SECURITY ISSUES IN WEB SYSTEMS (The Conference Hub, 2025)
Nowadays, along with the rapid development of Internet technologies, ensuring the security of web systems has become one of the urgent problems. This article analyzes the main security threats encountered in web systems and the reasons for their occurrence. In particular, types of attacks such as Malware, Phishing, DDOS attacks, Botnet, SQL injection, XSS (Cross-Site Scripting), CSRF (Cross-Site Request Forgery) are analyzed.